Formulasi Serbuk Wedang Tahu dan Pendugaan Umur Simpan Menggunakan Metode Kadar Air Kritis - Aliya Husna; Nurheni Sri Palupi; Feri Kusnandar; Azis Boing Sitanggang (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2024)
Indonesia silken tofu dessert is a traditional dish made from silken tofu and ginger sauce. To enhance its shelf life, this study explored the development of silken tofu dessert into a powdered form. Traditionally, silken tofu is coagulated using calcium sulfate (CaSO₄), but there has been little research on the optimal concentration of CaSO₄ necessary for forming curd in powdered silken tofu comparable to the traditional version. This study aimed to identify the ideal concentration of CaSO₄ as a coagulant to be added to powdered silken tofu and to estimate its shelf life using the critical moisture method. Sensory testing was conducted to select the appropriate concentration of CaSO₄, comparing different levels to a control method. The results revealed significant differences between the powdered silken tofu dessert and the traditional counterpart. Among the three CaSO₄ concentrations tested (3, 5, and 7%), the dessert prepared with 3% CaSO₄ exhibited the closest resemblance to the traditional silken tofu dessert. A single serving of this powdered silken tofu dessert provides 125 kcal of total energy, accounting for 12% of the recommended daily allowance (RDA) for protein, 3% for total fat, and 6% for carbohydrates. When packaged in metallized plastic and stored at a relative humidity of 78% and a temperature of 30 °C, the shelf life of the powdered silken tofu dessert is extended up to 12 months.